Financial Statement Fraud Perspective of Fraud Diamond Theory: Empirical Study on Consumer Cyclicals Sector Companies in Indonesia - Pranoto, Sarastanto Aulia Heru; Putra, Mukhlas Adi (JAFFA, 2025)
The purpose of this study is to examine the potential for financial statement fraud using fraud diamond theory factors such as stimulus (financial targets and external pressure), opportunity (ineffective monitoring), rationalization (auditor switching), and capacity (change in director and CEO duality). The sample of this research is consumer cyclical sector companies listed on the Indonesia Stock Exchange in 2020 - 2023, with a total sample of 492. The results of this study indicate that the variables of financial targets, external pressure, ineffective monitoring, and CEO duality have a significant effect on financial statement fraud. Still, the variables of auditor switching and change in director have no significant effect on financial statement fraud. A company needs to have a system to prevent fraudulent financial reporting with steps the company must set accurate and realistic financial targets, manage both internal and external pressures, create a review, detection, and monitoring policy system on human resources (HR), and avoid CEO dualism.